2020
DOI: 10.3389/fneur.2020.00287
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Intracerebral Giant Cell Arteritis

Abstract: Background: Giant cell arteritis (GCA) is the most common primary systemic vasculitis predominantly affecting large and medium sized vessels. In rare cases, the vasculitis can affect the vessels of the brain. Results: We describe four cases of GCA with involvement of the cerebral vessels causing stroke. These cases were unresponsive to aggressive immunosuppression and we opted to treat with endovascular balloon dilatation of the stenotic areas. The procedure was safe. The four patients were treated in nine ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Endovascular balloon dilatation of the stenotic areas has been attempted in GCA patients with involvement of the cerebral vessels causing stroke where aggressive immunosuppression was unsuccessful. 187,188…”
Section: Endovascular Treatmentmentioning
confidence: 99%
“…Endovascular balloon dilatation of the stenotic areas has been attempted in GCA patients with involvement of the cerebral vessels causing stroke where aggressive immunosuppression was unsuccessful. 187,188…”
Section: Endovascular Treatmentmentioning
confidence: 99%
“…Initial query of the databases identified 55 studies after duplicates were removed. Of these, nine studies were included in the analysis [ 20 – 28 ] after excluding cases in which GCA was not the diagnosis or the endovascular treatment did not involve intracranial vessels. The demographic, clinical, and technical details of each study are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…of Treatments Technique Target Vessel CV Risk Factors ESR CRP Corticosteroid treatment a Adjuvant Immunosuppressant a Vascular medications a Complications Clinical outcome b Clinical follow-up (days) 1 Simonsen et al. 2020 [ 20 ] 1 65F 2 PTA LICA None 46 NR Prednisone 1 mg/kg → solumedrol → prednisone taper CPM 15 mg/kg → tocilizumab → oral CPM × 6 mo, then methotrexate NR 1 MRS 2 90 2 64F 3 PTA LICAx3, RICAx2 HTN, DM 57 NR Prednisone 1 mg/kg → solumedrol → CPM 15 mg/kg × 6 → methotrexate NR Dissection x1, PCP pneumonia MRS 3 90 3 72M 2 PTA LICAx3, RICAx1, LVx1 HTN, smoking 22 NR Prednisone taper 1 mg/kg → solumedrol → prednisone taper CPM 10 mg/kg × 6 NR 0 MRS 1 90 4 71F 2 PTA LICAx2, RICAx2, LVx1 HTN 54 NR Solumedrol 1 mg/d → CPM 15 mg/kg × 6 NR Dissection x1 MRS 4 90 2 Lago et al. 2020 [ 21 ] 5 72F 1 PTA LICA HTN 50 NR Prednisone, ‘megadose’steroids dose NR None ASA during hospitalizat...…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, previous studies report successful endovascular treatment in patients with progressive intracranial stenosis in GCA. [28][29][30][31][32] However, reports of endovascular intervention with favorable results are more likely to be published than failed attempts. On the other side, these data must be judged considering the retrospective study design.…”
Section: Discussionmentioning
confidence: 99%